Risk Factors of HIV among Male Military Personnels: A Meta Analysis - Ayu Anulus; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Military personnel has a high risk of being exposed to HIV. The transmission of HIV from male military personnel is like an iceberg phenomenon. Based on studies in the US, UK, and France, the military personnel from these countries are much more likely to be contaminated with HIV than the equal age/sex group in the civilian population. This study aimed to analyze the risk factors of HIV among male military personnel by using meta-analysis.Subjects and Method: This study was a systematic and meta-analysis study. The articles used in this study were obtained from several electronic databases including PubMed, Scopus, Springer Link, ScienceDirect, and Clinical key. These articles were collected for 2 weeks. The keywords used in searching for the articles were as follows: